The Communication Patterns of Fathers in Developing Children's Science Proficiency in the Era of Artificial Intelligence - Dyah Ageng Pramesty Koenarso; Fadilla Ayuningtyas (Universitas Negeri Makassar, 2024)
This article focuses on analyzing fathers' communication patterns in shaping early childhood science skills in the era of Artificial Intelligence (AI). The main problem identified is the changing dynamics of communication between fathers and children, and its potential impact on the development of children's science skills. The purpose of this study is to identify effective father communication patterns in stimulating children's interest and science skills in the AI era. The research method was qualitative case study of five fathers. Data were collected through interviews, observations, and content analysis of father-child interactions in the context of science learning. Then analyzed using the Miles Huberman model and then data validity with data triangulation. The results showed that father's communication focused on open-ended questions, presenting information with a creative approach, and using AI technology as a learning tool can improve children's science skills. Fathers' understanding and support of technological development is also a key factor in building children's science literacy in the AI era. The findings contribute to practical understanding for parents, educators and policy makers to shape a communication environment that supports the development of children's science skills. The practical implications can be applied in designing family education programs and science learning strategies for early childhood that are appropriate to the development of AI technology.